Incidence of asymptomatic neurosyphilis in serofast Chinese syphilis patients - Cai, Sheng Nan (Sci Rep, 2017)
More new diagnosed syphilis cases were reported in china, the incidence and relevant factors of asymptomatic neurosyphilis (ANS) in serofast syphilis patients were unclear. Clinical and laboratory data of 402 Human Immunodeficiency Virus (HIV) negative, serofast syphilis patients, who underwent lumbar puncture at the Peking University Ditan Teaching Hospital between September 2008 and August 2016, were collected. Incidence of ANS was verified and the relevant factors were further analyzed. According to the ANS criteria, 139 (34.6%) patients had ANS. Of these, 40 (28.8%) had reactive cerebrospinal fluid (CSF), rapid plasma reagin (RPR) positive, 115 (82.7%) had CSF white blood cell (WBC) count > 5 × 10(6)/L, 28 (20.1%) had CSF protein concentration > 45 mg/dL (without other neurological diseases). Patients aged 51–60 years, of non-Han ethnicity, with serum RPR titer 1:32 and ≥ 1:64 were 2.28-fold, 9.11-fold, 5.12-fold and 5.69-fold, respectively, more likely to have ANS. The incidence of ANS was 34.6% among Chinese serofast syphilis patients. Age, ethnicity and serum RPR titer were associated with high risk of ANS.